Amplifying the Whispers: A Critical Gendered Examination of Fraternal Culture. Issue 164 (1st November 2018) - Nicolazzo, Z; Karikari, Shamika N.
Abstract: As a functional unit, fraternity and sorority life has often—and many would argue rightly—been critiqued for its perpetuation of hegemonic ideologies, spaces, and student demographics. In this chapter, the authors use critical theoretical perspectives to explore alternative possibilities for professional practice in fraternity life.